Comprehensive characterization of a floral mutant reveals the mechanism of hooked petal morphogenesis in Chrysanthemum morifolium. Issue 12 (26th May 2019) - Ding, Lian; Zhao, Kunkun; Zhang, Xue; Song, Aiping; Su, Jiangshuo; Hu, Yueheng; Zhao, Wenqian; Jiang, Jiafu; Chen, Fadi
Summary: The diversity of form of the chrysanthemum flower makes this species an ideal model for studying petal morphogenesis, but as yet, the molecular mechanisms underlying petal shape development remain largely unexplored. Here, a floral mutant, which arose as a bud sport in a plant of the variety 'Anastasia Dark Green', and formed straight, rather than hooked petals, was subjected to both comparative morphological analysis and transcriptome profiling. The hooked petals only became discernible during a late stage of flower development. At the late stage of 'Anastasia Dark Green', genes related to chloroplast, hormone metabolism, cell wall and microtubules were active, as were cell division‐promoting factors. Auxin concentration was significantly reduced, and a positive regulator of cell expansion was down‐regulated. Two types of critical candidates, boundary genes and adaxial–abaxial regulators, were identified from 7937 differentially expressed genes in pairwise comparisons, which were up‐regulated at the late stage in 'Anastasia Dark Green' and another two hooked varieties. Ectopic expression of a candidate abaxial gene, CmYAB1, in chrysanthemum led to changes in petal curvature and inflorescence morphology. Our findings provide new insights into the regulatory networks underlying chrysanthemum petal morphogenesis.